Pengaruh Likuiditas, Leverage, Ukuran Perusahaan terhadap Profitabilitas dan Opini Audit dengan Reputasi Kap Sebagai Moderasi pada Perusahaan Sektor Pertambangan dan Energi yang Terdaftar di Bursa Efek Indonesia - Amelia Vega Buana; Tri Ratnawati (AKUNTANSI 45, 2026)
With profitability serving as an intervening variable and audit firm reputation as a moderating variable, this study attempts to investigate the impacts of liquidity, Leverage, and company size on profitability and audit opinion. Purposive sampling was used to choose samples based on the availability and completeness of secondary data, which was gathered from the financial statements of mining and energy sector businesses listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period. Using SmartPLS software, the Partial Least Squares (PLS) approach was used to analyze the data. The findings show that while business size has no discernible impact on profitability, liquidity and Leverage do. Additionally, while business size has a considerable negative impact on audit opinion, liquidity and Leverage have a significant impact. Profitability cannot serve as an intervening variable since it has no discernible impact on audit opinion. Additionally, the moderation test shows that the impact of profitability on audit opinion is not much mitigated by audit firm reputation. These findings are anticipated to aid in a deeper comprehension of audit opinion determinants for scholars, auditors, and stakeholders. They emphasize the significance of taking firm-specific financial factors into account when evaluating the likelihood of audit opinion issuance, particularly in high-risk industries like mining and energy.